Magnetic Resonance Imaging in Otosyphilis: A Rare Manifestation of Neurosyphilis - Chandrasekharan, Rajsekar; Kulkarni, Chinmay; Pullara, Sreekumar Karumathil; Moorthy, Srikanth (Indian Journal of Radiology and Imaging, 2022)
We report magnetic resonance imaging (MRI) in a case with otosyphilis, which is a rare manifestation of neurosyphilis. A 50-year-old male presented with progressive hearing loss on the left side and recent-onset palsy of the left 7th and 12th cranial nerves. Computed tomography imaging showed destructive bone lesions involving the petrous temporal bone, middle ear, and mastoid region with a pathognomonic pattern of bone destruction depicted in the volume rendering technique images. MRI showed features of destructive bone lesions (gummatous lesion), meningoneuritis, and labyrinthitis. Pathological examination and treponemal antibody absorption test favored the diagnosis. Otosyphilis should be considered as a differential diagnosis in an adult patient with destructive lesions of the petrous temporal bone. To the best of our knowledge, MRI in otosyphilis has not been reported.
Keywords: gummatous lesions; labyrinthitis; meningoneuritis; neurosyphilis; otosyphilis